The Influence of Green Marketing and Green Product Strategies on Purchasing Decisions (Case Study: Le Minerale Gallon Water in Lampung) - Nina Lelawati; Elmira Febri Darmayanti; Fitriani Fitriani; Karnila Ali; Nani Septiana (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to demonstrate the efficiency and effectiveness of Green Marketing. We use a case study approach focusing on the branding efforts of Le Minerale's single-use gallon water, which has gained recognition recently. Initially considered environmentally unfriendly, Le Minerale attempted to counter this perception through extensive promotion incorporating strong environmental elements and the principles of Green Marketing. To support this Green Marketing effort, they also sought to convince consumers that their gallon water is a Green Product, featuring easily recyclable packaging and water that does not undergo chemical processes. To measure Green Marketing and Green Product, we utilized the following indicators: the presence of eco labels, environmental advertisements, and eco brands. The quantitative data analysis technique we employed is the associative method to determine the relationship between two or more variables. We also conducted Focus Group Discussions and interviews to reinforce our findings, in addition to relying on Likert scale-based questionnaires. Our goal is to produce a journal and scientific report explaining the relationship between Green Product and Green Marketing as independent variables influencing the purchasing decision of Le Minerale gallon water. For data processing, we have prepared SPSS technology. We hope that this research can serve as a foundation for studies on the importance of environmentally-focused promotion. Below is our research proposal on the effectiveness of Green Marketing and Green Product on the purchasing decision of Le Minerale gallon water.